Thick KNbO 3 films deposited by ultrasonic-assisted hydrothermal method - Kudo, Ryo; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (Acoustical Science and Technology)

Advantages of reliability-adaptive system operation for maintenance planning - Meyer, Tobias; Kaul, Thorben; Sextro, Walter (Proceedings of the 9th IFAC Symposium on Fault Detection, Supervision and Safety for Technical Processes)
Intelligent mechatronic systems other the possibility to adapt system behavior to current dependability. This can be used to assure reliability by controlling system behavior to reach a pre-defined lifetime. By using such closed loop control, the margin of error of useful lifetime of an individual system is lowered. It is also possible to change the pre-defined lifetime during operation, by adapting system behavior to derate component usage. When planning maintenance actions, the remaining useful lifetime of each individual system has to be taken into account. Usually, stochastic properties of a fleet of systems are analyzed to create maintenance plans. Among these, the main factor is the probability of an individual system to last until maintenance. If condition-based maintenance is used, this is updated for each individual system using available information about its current state. By lowering the margin of error of useful lifetime, which directly corresponds to the time until maintenance, extended maintenance periods are made possible. Also using reliability-adaptive operation, a reversal of degradation driven maintenance planning is possible where a maintenance plan is setup not only according to system properties, but mainly to requirements imposed by maintenance personnel or infrastructure. Each system then adapts its behavior accordingly and fails according to the maintenance plan, making better use of maintenance personnel and system capabilities at the same time. In this contribution, the potential of maintenance plan driven system behavior adaptation is shown. A model including adaptation process and maintenance actions is simulated over full system lifetime to assess the advantages gained.
Keywords: Adaptive systems; Reliability analysis; Availability; Adaptive control; Maintenance; Self-optimizing systems; Self-optimizing control; Stochastic Petri-nets

Anforderungen an Condition-Monitoring-Verfahren zur Nutzung im zuverläsigkeitsgeregelten Betrieb adaptiver Systeme - Meyer, Tobias; Kimotho, James Kuria; Sextro, Walter (27. Tagung Technische Zuverlässigkeit (TTZ 2015) - Entwicklung und Betrieb zuverlässiger Produkte)
Intelligente technische Systeme, die in der Lage sind, sich an geänderte Umgebungsbedingungen anzupassen, ermöglichen eine Adaption anhand der aktuell erreichten Zuverlässigkeit. Zu diesem Zwecke kann ein geschlossener Regelkreis formuliert werden, der dazu geeignet ist, den Betriebspunkt des Systems während der gesamten Lebensdauer anzupassen. Dadurch wird eine harte Umschaltung während des Betriebs vermieden und die Verhaltensanpassung ist vom Nutzer weitgehend unbemerkt möglich. Dazu wird die aktuelle Restlebensdauer mit einer vorgegebenen Restlebensdauer verglichen. Durch Änderung der vorgegebenen Restlebensdauer lässt sich auch eine Anpassung der gewünschten Nutzungsdauer erreichen, beispielsweise um veränderte Wartungsintervalle einzuhalten. Zu diesem Zwecke ist es allerdings notwendig, die aktuell erreichte Zuverlässigkeit zu schätzen. Für die Regelung ist dabei die aktuelle Restlebensdauer der wichtigste Parameter, da er als Istwert direkt mit der gewünschten Restlebensdauer als Sollwert verglichen wird und als Reglereingang dient. Für die Genauigkeit der Regelung ist daher die Bestimmung der Restlebensdauer von entscheidender Bedeutung. Es wird ein Modell des Regelkreises vorgestellt, das auch den Einfluss einer fehlerhaften Restlebensdauerschätzung auf die Verhaltensanpassung abbildet. Dadurch ist es möglich, Grenzen der Verhaltensanpassung und die zur Einhaltung notwendige Genauigkeit der Restlebensdauerschätzung zu bestimmen. Es gibt zahlreiche Ansätze, die Restlebensdauer zu schätzen, die aufgeteilt werden in modellbasierte Verfahren und datengetriebene Verfahren. Die individuelle Eignung eines jeden Verfahrens sowie die Modellbildung oder die Nutzung geeigneter Algorithmen ist stark systemabhängig. Um die Auswahl von Verfahren und Modellen oder Algorithmen zu ermöglichen, werden zunächst die Anforderungen an die Restlebensdauerschätzung zur Nutzung als Regelungs-Istwert bestimmt. Verschiedene Verfahren werden sodann hinsichtlich ihrer Eignung evaluiert und Anwendungsgrenzen aufgezeigt.

Modeling and simulation of the ultrasonic wire bonding process - Meyer, Tobias; Unger, Andreas; Althoff, Simon; Sextro, Walter; Brökelmann, Michael; Hunstig, Matthias; Guth, Karsten (2015 17th Electronics Packaging Technology Conference)
Ultrasonic wire bonding is an indispensable process in the manufacturing of semiconductor components. It is used for interconnecting the silicon die to e.g. connectors in the housing or to other semiconductors in complex components. In high power applications, such as wind turbines, locomotives or electric vehicles, the thermal and mechanical limits of interconnects made from aluminum are nearing. The limits could be overcome using copper wire bonds, but their manufacturing poses challenges due to the harder material, which leads to increased wear of the bond tools and to less reliable production. To overcome these drawbacks, adaptation of process parameters at runtime is employed. However, the range of parameter values for which a stable process can be maintained is very small, making it necessary to compute suitable parameters beforehand. To this end, and to gain insights into the process itself, the ultrasonic bonding process is modeled. The full model is composed of several partial models, some of which were introduced before. This paper focuses on the modularization of the full model and on the interaction of partial models. All partial models are presented, their interaction is shown and the general outline of the simulation process is given.

A Mechanical Model for the Dynamical Contact of Elastic Rough Bodies with Viscoelastic Properties - Schulte, Frank; Neuhaus, Jan; Sextro, Walter (Proceedings of ICoEV 2015 International Conference on Engineering Vibration)
The contact between viscoelastic materials e.g. elastomers and a rough surface leads to a special friction characteristic, which differs greatly in its properties comparing to other materials like metals. In practice, this friction combination occurs for example in the tire-road contact, or in the use of rubber gaskets. Due to the frictional forces a system is significantly influenced in its vibrational properties. The friction force is composed of two main components adhesion and hysteresis. The adhesion results from molecular bounds between the contact partners, while the deformation of the viscoelastic material by the roughness of the counter body leads to power loss. This internal friction results in an additional frictional force, which is described by the hysteresis. To simulate the frictional behaviour of elastomers on rough surfaces and thus to determine the energy dissipation in contact, it is necessary to develop a mechanical model which considers the roughness of the contact partners, as well as dynamic effects and the dependence on normal pressure and sliding speed. The viscoelastic material behaviour must also be considered. The contact between two rough surfaces is modelled as a rough rigid layer contacting a rough elas- tic layer. The elastic layer is modelled by point masses connected by Maxwell-elements. This allows the viscoelastic properties of the elastomer to be considered. The behaviour of whole system can be described by equations of motion with integrated constraints. The degrees of freedom of the model depends on the varying contact conditions. A point mass not in contact has two degrees of freedom. A point mass in contact moving along the roughness path can be described by only one degree of freedom. For each Maxwell-Element also an inner coordinate and thus a further degree of freedom is needed. Because of varying contact conditions dur- ing the simulation, the simulation interrupts in case the contact conditions change. Then the equations of motions are adapted with respect to the contact constraints. As a result of the simulation one obtain the energy dissipation and thus the friction char- acteristic during the friction process. It is possible to use these results in three dimensional point-contact elements in order to model contact surfaces on lager length scales.
Keywords: Contact Mechanics; Viscoelastic Material; Adhesive Friction; Hysteresis Friction; Energy Dissipation; Vibration

Modeling of the Stick-Slip Effect in Heavy Copper Wire Bonding to Determine and Reduce Tool Wear - Unger, Andreas; Sextro, Walter; Meyer, Tobias; Eichwald, Paul; Althoff, Simon; Eacock, Florian; Brökelmann, Michael (2015 17th Electronics Packaging Technology Conference)
To increase quality and reliability of copper wire bonds, self-optimization is a promising technique. For the implementation of self-optimization for ultrasonic heavy copper wire bonding machines, a model of stick-slip motion between tool and wire and between wire and substrate during the bonding process is essential. Investigations confirm that both of these contacts do indeed show stick-slip movement in each period oscillation. In a first step, this paper shows the importance of modeling the stick-slip effect by determining, monitoring and analyzing amplitudes and phase angles of tool tip, wire and substrate experimentally during bonding via laser measurements. In a second step, the paper presents a dynamic model which has been parameterized using an iterative numerical parameter identification method. This model includes Archard's wear approach in order to compute the lost volume of tool tip due to wear over the entire process time. A validation of the model by comparing measured and calculated amplitudes of tool tip and wire reveals high model quality. Then it is then possible to calculate the lifetime of the tool for different process parameters, i.e. values of normal force and ultrasonic voltage.

Minimizing Expectation Plus Variance - Monien, Burkhard; Mavronicolas, Marios (Theory of Computing Systems)
We consider strategic games in which each player seeks a mixed strategy to minimize her cost evaluated by a concave valuation V (mapping probability distributions to reals); such valuations are used to model risk. In contrast to games with expectation-optimizer players where mixed equilibria always exist (Nash 1950; Nash Ann. Math. 54, 286–295, 1951), a mixed equilibrium for such games, called a V-equilibrium, may fail to exist, even though pure equilibria (if any) transfer over. What is the exact impact of such valuations on the existence, structure and complexity of mixed equilibria? We address this fundamental question in the context of expectation plus variance, a particular concave valuation denoted as RA, which stands for risk-averse; so, variance enters as a measure of risk and it is used as an additive adjustment to expectation. We obtain the following results about RA-equilibria:A collection of general structural properties of RA-equilibria connecting to (i) E-equilibria and Var-equilibria, which correspond to the expectation and variance valuations E and Var, respectively, and to (ii) other weaker or incomparable properties such as Weak Equilibrium and Strong Equilibrium. Some of these structural properties imply quantitative constraints on the existence of mixed RA-equilibria.A second collection of (i) existence, (ii) equivalence and separation (with respect to E-equilibria), and (iii) characterization results for RA-equilibria in the new class of player-specific scheduling games. We provide suitable examples with a mixed RA-equilibrium that is not an E-equilibrium and vice versa.A purification technique to transform a player-specific scheduling game on two identical links into a player-specific scheduling game on two links so that all non-pure RA-equilibria are eliminated while no new pure equilibria are created; so, a particular player-specific scheduling game on two identical links with no pure equilibrium yields a player-specific scheduling game with no RA-equilibrium (whether mixed or pure). As a by-product, the first PLS-completeness result for the computation of RA-equilibria follows.

RSDL workbench results for OAEI 2015 - Schwichtenberg, Simon; Engels, Gregor (Proceedings of the 10th International Workshop on Ontology Matching collocated with the 14th International Semantic Web Conference (ISWC 2015), Bethlehem, PA, USA, October 12, 2015.)

Self-assembled nanogap electrodes for the directed assembly of nanoparticles - Brassat, Katharina; Brodehl, Christoph; Lindner, Jörg

Self-assembled Nanogap Electrodes in Microﬂuidic Channels - Brassat, Katharina; Brodehl, Christoph; Lindner, Jörg

Three-dimensional analysis of mask-clogging effects on the morphology of nanoparticles fabricated by nanosphere lithography - Brodehl, Christoph; Riedl, Thomas; Greulich-Weber, Siegmund; Lindner, Jörg

How to create billions of tailored plasmonic nanoparticles in half an hour - Brodehl, Christoph; Greulich-Weber, Siegmund; Lindner, Jörg

Correlation between defect densities in colloidal nanosphere masks and experimental parameters - Drude, Dennis; Brassat, Katharina; Brodehl, Christoph; Lindner, Jörg

An Algorithm for Tailoring of Nanoparticles by Double Angle Resolved Nanosphere Lithography - Brodehl, Christoph; Greulich-Weber, Siegmund; Lindner, Jörg (MRS Proceedings)

Investigation of cubic GaN quantum dots grown by the Stranski-Krastanov process - Bürger, M.; Lindner, Jörg; Reuter, Dirk; As, D. J. (physica status solidi (c))
We investigate the formation of cubic GaN quantum dots (QDs) on pseudomorphic strained cubic AlN layers on 3C-SiC (001) substrates grown by means of molecular beam epitaxy. Surface morphologies of various QD sizes and densities were obtained from uncapped samples by atomic force microscopy. These results were correlated with similar but capped samples by photoluminescence experiments. The QD density varies by one order of magnitude from ~1x10^10 cm^-2 to ~1x10^11 cm^-2 as a function of the GaN coverage on the surface. The initial layer thickness for the creation of cubic GaN QDs on cubic AlN was obtained to 1.95 monolayers by a comparison between the experimental results and an analytical model. Our results reveal the strain-driven Stranski-Krastanov growth mode as the main formation process of the cubic GaN QDs.

Self-Arrangement of Colloidal Au Nanoparticles in SiO2-Nanopores fabricated by Block-Copolymer Lithography - Garozzo, C.; Brassat, Katharina; La Magna, A.; Puglisi, R.A.; Lindner, Jörg

STEM-CL investigations on the influence of stacking faults on the optical emission of cubic GaN epilayers and cubic GaN/AlN multi-quantum wells - Kemper, R. M.; Veit, P.; Mietze, C.; Dempewolf, A.; Wecker, T.; Bertram, F.; Christen, J.; Lindner, Jörg; As, D. J. (physica status solidi (c))
We report the influence of {111} stacking faults on the cathodoluminescence (CL) emission characteristics of cubic GaN (c-GaN) films and cubic GaN/AlN multiquantum wells. Transmission electron microscopy (TEM) measurements indicate that stacking faults (SFs) on the {111} planes are the predominant crystallographic defects in epitaxial films, which were grown on 3CSiC/ Si (001) substrates by plasma-assisted molecular beam epitaxy. The correlation of the SFs and the luminescence output is evidenced with a CL setup integrated in a scanning TEM (STEM). By comparing the STEM images and the simultaneously measured CL signals it is demonstrated that SFs in these films lead to a reduced CL emission intensity. Furthermore, the CL emission intensity is shown to increase with increasing film thickness and decreasing SF density. This correlation can be connected to the reduction of the full width at half maximum of X-ray diffraction rocking curves with increasing film thickness of c-GaN films.

Stability of heteroepitaxial coherent growth modes on nanowire radial surfaces - Riedl, Thomas; Lindner, Jörg

A molecular statics study of strain fields and defect stability in axial-heteroepitaxial nanopillars - Riedl, Thomas; Lindner, Jörg

Making things small – for fun and for serious applications - Lindner, Jörg